2016
DOI: 10.1055/s-0042-110855
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of Propiverine Contribute to Improving Lower Urinary Tract Dysfunctions in Rats with Spinal Cord Injuries

Abstract: Patients with spinal cord injury (SCI) usually develop lower urinary tract dysfunctions, including detrusor overactivity which is also known to be a risk factor for upper urinary tract dysfunction. Antimuscarinic agents, such as propiverine, have been used clinically for the treatment of detrusor overactivity. Also, propiverine has been known to possess antagonistic activity against L-type Ca channels and transient receptor potential vanilloid subtype 1 (TRPV1), in addition to activity against muscarinic recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Previous studies suggested that the NVC in SCI rats are mediated predominantly by C‐fiber afferents in urothelial and suburothelial layers while A δ‐fiber afferents are involved in voiding reflexes in normal rats . In addition, mounting evidence indicates that M 3 receptor may play an important role in the NDO after SCI, resulting from those results that activation of muscarinic receptor could enhance NDO through increasing C‐fiber afferents mediated activity in SCI rats and muscarinic receptor antagonists participated in the desensitization of C‐fiber afferents . For example, Iijima et al found that systemic administration of M 3 receptor selective antimuscarinic agent suppressed the activity of bladder afferent C fibers in rats during bladder filling .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggested that the NVC in SCI rats are mediated predominantly by C‐fiber afferents in urothelial and suburothelial layers while A δ‐fiber afferents are involved in voiding reflexes in normal rats . In addition, mounting evidence indicates that M 3 receptor may play an important role in the NDO after SCI, resulting from those results that activation of muscarinic receptor could enhance NDO through increasing C‐fiber afferents mediated activity in SCI rats and muscarinic receptor antagonists participated in the desensitization of C‐fiber afferents . For example, Iijima et al found that systemic administration of M 3 receptor selective antimuscarinic agent suppressed the activity of bladder afferent C fibers in rats during bladder filling .…”
Section: Discussionmentioning
confidence: 99%
“…17 In addition, mounting evidence indicates that M 3 receptor may play an important role in the NDO after SCI, resulting from those results that activation of muscarinic receptor could enhance NDO through increasing C-fiber afferents mediated activity in SCI rats and muscarinic receptor antagonists participated in the desensitization of C-fiber afferents. [17][18][19][20] For example, Iijima et al found that systemic administration of M 3 receptor selective antimuscarinic agent suppressed the activity of bladder afferent C fibers in rats during bladder filling. 21 In addition to the direct muscarinic control of bladder afferent pathways, another possible mechanism by which downregulating M 3 receptor expression decreases NVC might be related to ATP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there are medicines with anticholinergic and calcium antagonist properties to synergistically reduce the anormal contractions of bladder due to inestability or hiperactivity of detrusor (Sugaya et al 2012). To this therapeutic group belong oxybutinine and propiverine, which have strong anticholinergic activity but weak effect as calcium channels blocker (Hamada et al, 1997;Sakakibara et al 2016). Other…”
Section: Discussionmentioning
confidence: 99%